2014
DOI: 10.1007/s00221-014-4149-9
|View full text |Cite
|
Sign up to set email alerts
|

Towards a constructionist approach to emotions: verification of the three-dimensional model of affect with EEG-independent component analysis

Abstract: The locationist model of affect, which assumes separate brain structures devoted to particular discrete emotions, is currently being questioned as it has not received enough convincing experimental support. An alternative, constructionist approach suggests that our emotional states emerge from the interaction between brain functional networks, which are related to more general, continuous affective categories. In the study, we tested whether the three-dimensional model of affect based on valence, arousal, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 80 publications
2
23
0
1
Order By: Relevance
“…On the other hand, the temporal poles, which are considered by some authors to constitute an "extended limbic system," also are related to processing of emotional stimuli (Olson, Plotzker, & Ezzyat, 2007). In line with the current results, activity of the left anterior temporal cortex has been shown to increase together with subjective ratings of negative emotions in response to negatively valenced stimuli (Wyczesany & Ligeza, 2014). Consistently with the activation of the right OFC, for which a similar modulation pattern was observed in the overlapping time window (188-288 ms), the pattern of amygdala/LATmp modulation could reflect the process of affective elaboration of pain stimuli.…”
Section: Temporal Sequence Of Neural Modulationsupporting
confidence: 90%
“…On the other hand, the temporal poles, which are considered by some authors to constitute an "extended limbic system," also are related to processing of emotional stimuli (Olson, Plotzker, & Ezzyat, 2007). In line with the current results, activity of the left anterior temporal cortex has been shown to increase together with subjective ratings of negative emotions in response to negatively valenced stimuli (Wyczesany & Ligeza, 2014). Consistently with the activation of the right OFC, for which a similar modulation pattern was observed in the overlapping time window (188-288 ms), the pattern of amygdala/LATmp modulation could reflect the process of affective elaboration of pain stimuli.…”
Section: Temporal Sequence Of Neural Modulationsupporting
confidence: 90%
“…For example, Moors et al ( 2013 ) used power or control (Fontaine et al, 2007 ) as an example of the dominance dimension (ranging from weak/submissive to strong/dominant). Dominance dimension, as well as valence and arousal, was found to reflect brain activity connected with current mood in a more coherent way than the traditional approach in mood description based on discrete emotional states (e.g., Wyczesany and Ligeza, 2015 ).…”
Section: Introductionmentioning
confidence: 85%
“…Because the multi-dimensional model assumes independence of psychological axes and their corresponding neural markers, it would be necessary to confirm EEG features selected for each axis would be dissociable. For example, a previous study suggests that multiple ICs would be loaded on one axis and that one IC might also contributing to the other axes to some extent [39]. In addition, studies support a view that the functions of a brain region are ubiquitous and not limited to a unitary and discrete function [6].…”
Section: Corresponding Electrophysiological Markers For the Three Axesmentioning
confidence: 74%
“…Previous neuroimaging research suggests a source in proximity to orbitofrontal areas may be responsible for emotional valence [38]. A similar EEG study [39] related EEG features to the subjective feeling at rest, rather than during a task based on another type of 3-D emotional space (valence, arousal, and dominance, also known as the PAD model). By focusing only on the β-band power of IC clusters, they found that IC clusters with sources localized in posterior cingulate and right posterior temporal lobe were positively correlated with valence.…”
Section: Ic Markers Of Valencementioning
confidence: 85%